Inhibition of CD38 enzyme activity on engrafted human immune cells enhances NAD+ metabolism and inhibits inflammation in an in-vivo model of xeno-GvHD - Ahmil-Boiteau, Ghenima; Dalvi, Pranjali; Dang, Kevin; Ugamraj, Harshad S.; Castello, Giulia; Allison, James; Schellenberger, Ute; Buelow, Roland; Iyer, Suhasini; Buelow, Ben; Chini, Eduardo; Blazar, Bruce; et al. (Frontiers in Immunology, 2025)
IntroductionCD38 is highly expressed on immune cells. It catabolizes NAD+, which is a critical cofactor for enzymes involved in metabolism and energy production. Methods and resultsWe developed TNB-738, a fully human antibody that potently inhibits human CD38 enzymatic activity on human immune cells, resulting in a dose-dependent increase of intracellular NAD+ levels. TNB-738 does not show immune effector functions, does not induce direct cell killing of CD38 positive cells and is not internalized. In vivo, treatment with TNB-738 following infusion of human PBMCs into NSG mice resulted in significantly lower clinical scores, prolonged overall survival, less expansion of engrafted human CD45+ cells and a significant expansion of Tregs. DiscussionCD38 positive T cells regulate NAD+ metabolism in inflamed tissues and blockade of CD38 enzyme activity by TNB-738 could represent a novel class of therapeutics for the treatment of inflammatory conditions, including GvHD.